Analisis Sistem Informasi Penerimaan Mahasiswa Baru Dengan Cobit Framework - Willy Riyadi; Xaverius Sika; Eni Rohaini (Jurnal PROCESSOR, 2017)
Information quality of an information system required three aspects: the input, process, and output. If one of the three aspects is not executed properly then the resulting information will be distorted and will not be in accordance with academic needs so that there will be various losses both from the aspect of prospective students concerned and academics who manage the data of new students. STIKOM Dinamika Bangsa Jambi is one of the campuses that move in computer science education in jambi. In the past, the new student admissions activities are still offline and fill out the forms provided by the committee. Currently, STIKOM Dinamika Bangsa Jambi has created a new student admissions information system and is online in supporting and simplify prospective students in registering themselves as students at STIKOM Dinamika Bangsa Jambi. Therefore, this study aims to measure the maturity level of information systems of new admissions STIKOM Dinamika Bangsa Jambi using Monitor, Evaluate and Assess (MEA01) domain with interview method and questionnaire of Process Capability Model (PCM), so it can be known the current condition (as is) with the expected conditions (to be) by prospective new students who want to register as well as the internal STIKOM Dinamika Bangsa Jambi namely Front Office and Biro Administrasi Akademik dan Kemahasiswaan (BAAK).